Timely Pulmonary Valve Replacement May Allow Preservation of Left Ventricular Circumferential Strain in Patients with Tetralogy of Fallot - Burkhardt, Barbara E. U.; Velasco Forte, Marí Nieves; Durairaj, Saravanan; Rafiq, Isma; Valverde, Israel; Tandon, Animesh; Simpson, John; Hussain, Tarique (Frontiers in Pediatrics, 2017)
Introduction: Patients with Tetralogy of Fallot (TOF) and pulmonary insufficiency and a dilated right ventricle (RV) may suffer from a reduction in left ventricular (LV) performance. It is not clear whether timely pulmonary valve replacement (PVR) preserves LV mechanics. Methods: Ten TOF patients who underwent PVR were identified from hospital records, and pre- and postoperative CMR images were post-processed with a semi-automatic tissue tracking software. LV circumferential strain, time to peak strain, and torsion were compared before and after PVR. A control group of ten age-matched normal volunteers was assessed as a comparison. Results: LV circumferential strain did not change before versus after PVR (basal -18.3 +/- 3.7 % vs. -20.5 +/- 3 %, p 0.082; mid-ventricular -18.4 +/- 3.6 % vs. -19.1 +/- 2 %, p 0.571; apical -22.7 +/- 5.2 % vs. -22.1 +/- 4 %; p 0.703). There was also no difference seen between the baseline strain and normal controls (control basal -18.2 +/- 3.3 %, p 0.937; mid -18 +/- 3.2 %, p 0.798; apex -24.1 +/- 5 %, p 0.552). LV torsion remained unchanged from baseline to post PVR (systolic 2.75 (1.23 – 9.51) °/cm vs. 2.3 +/- 1.2 °/cm, p 0.285; maximum 5.5 +/- 3.5 °/cm vs. 2.34 (1.37 – 8.07) °/cm, p 0.083). There was no difference in time to measured peak LV circumferential strain before versus after PVR (basal 0.44 +/- 0.1 vs. 0.43 +/- 0.05, p 0.912; mid-ventricular 0.42 +/- 0.08 vs. 0.38 +/- 0.06, p 0.186; apical 0.40 +/- 0.08 vs. 0.40 +/- 0.06, p 0.995). At the same time, pulmonary regurgitation and RV end-diastolic and end-systolic volume indices decreased and LV end-diastolic volume increased after PVR. RV and LV ejection fractions remained constant. Conclusion: PVR allows for favorable remodeling of both ventricular volumes for TOF patients with significant pulmonary regurgitation. In this cohort, LV myocardial functional parameters such as circumferential strain, time to peak strain, and LV torsion were normal at baseline and remain unchanged after PVR.